The Shape of a Vehicle Windshield Affects Reaction Time and Brain Activity During a Target Detection Task - Sasaoka, Takafumi; Machizawa, Maro G.; Okamoto, Yoshihisa; Iwase, Koji; Yoshida, Toshihiro; Michida, Nanae; Kishi, Atsuhide; Chiba, Masaki; Nishikawa, Kazuo; Yamawaki, Shigeto; Nouzawa, Takahide (Frontiers in Human Neuroscience, 2020)
Background: Achieving clear visibility through a windshield is one of the crucial factors in manufacturing a safe and comfortable vehicle. The optic flow (OF) through the windshield has been reported to divert attention and could impair visibility. Although a growing number of behavioral and neuroimaging studies have assessed drivers’ attention in various driving scenarios, there is still little evidence of a relationship between OF, windshield shape, and driver’s attentional efficacy. The purpose of this research was to examine this relationship. Methods: First, we quantified the OF across the windshield in a simulated driving scenario with either of two types of windshield (a tilted or vertical pillar) at different speeds (60 km/h or 160 km/h) and found more upward OF along the tilted pillar than along the vertical pillar. Therefore, we hypothesized that the predominance of upward OF around the windshield along a tilted pillar could distract a driver and that we could observe the corresponding neural activity. Magnetic resonance scans were then obtained while the subjects performed a visual detection task while watching the driving scene used in the OF analysis. The subjects were required to press a button as rapidly as possible when a target appeared at one of five positions (leftmost, left, center, right, and rightmost). Results: We found that the reaction time on exposure to a tilted pillar was longer than that on exposure to a vertical pillar in the rightmost condition. Furthermore, there was more brain activity in the precuneus when the pillar was tilted than when it was vertical in the rightmost condition. In a separate analysis, activation in the precuneus was found to reflect relative changes in the amount of upward OF when the target was at the rightmost position. Conclusions: Overall, these observations suggest that activation in the precuneus may reflect extraneous cognitive load driven by upward OF along the pillar and could distract visual attention. The findings of this study highlight the value of a cognitive neuroscientific approach to research and development in the motor vehicle manufacturing industry.